Assessment of Maize and Soybean Pricing - Muhammad Firdaus; Fuza; Hastuti; Dea Amanda (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Prices of maize and soybean fluctuated significantly at both producer and consumer levels in Indonesia. This study aims to analyze the pricing of maize and soybean at the consumer level by employing the vector error correction model and to analyze the market behavior in determining consumer prices by using the game theory. The results show that maize prices at the consumer level are positively influenced by producer price, wholesale price, as well as gasoline price shocks and are also negatively affected by supply shocks. Soybean prices at the consumer level are negatively influenced by producer price shocks and are positively affected by wholesale price shocks. Shocks in terms of supply result in the fluctuating prices received by the consumers. It is due to the dominant pricing strategy, which is through collusion performed by the maize and soybean retailers. Some market efficiencies are encouraged to reach more stabilized prices. Keywords: game theory, maize, soybean, market efficiency